2019
DOI: 10.1155/2019/7478498
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Convergence Particle Swarm Optimization Algorithm with Random Sampling of Control Parameters

Abstract: Although particle swarm optimization (PSO) has been widely used to address various complicated engineering problems, it still needs to overcome the several shortcomings of PSO, e.g., premature convergence and low accuracy. Its final optimization result is related to the control parameters selection; therefore, an improved convergence particle swarm optimization algorithm with random sampling of control parameters is proposed. For the proposed algorithm, the random sampling strategy of control parameters is des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Also in order to utilize dimension information of particles with better velocity and position, the stochastic correction method is assumed on each dimension for the population prime value. The experimental results have shown that the method suggested improves the rate of convergence with increase in the accuracy of convergence as compared to basic PSO [5]…”
Section: ) Improved Convergence Pso With Random Sampling Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in order to utilize dimension information of particles with better velocity and position, the stochastic correction method is assumed on each dimension for the population prime value. The experimental results have shown that the method suggested improves the rate of convergence with increase in the accuracy of convergence as compared to basic PSO [5]…”
Section: ) Improved Convergence Pso With Random Sampling Mechanismmentioning
confidence: 99%
“…This section presents the basic principle of PSO, its variants in the research for achieving load balancing according to [5]-[22]…”
Section: Study Of Particle Swarm Optimizationmentioning
confidence: 99%
“…In pursuit of a better coverage technique, a majority of scholars have tried to use intelligent algorithms, like Genetic Algorithm (GA) [18] and Particle Swarm Optimization (PSO) [19], to solve the issue. Though the Fruit Fly Optimization Algorithm is more simple and practicable than GA and PSO, but due to unavoidable limitations, the researchers are still exerting their efforts to develop a shrewder algorithm.…”
Section: Artificial Bee Colony (Abc)mentioning
confidence: 99%
“…It can either be seen either as PSO with developing loads or as a transformative calculation with a development rule acquired from PSO. EPSO has just demonstrated to be proficient, precise and hearty, along these lines appropriate to power system issues [9][10].…”
Section: Evolutionary Particle Swarm Optimizationmentioning
confidence: 99%